Progressive anemia of prematurity is associated with a critical increase in cerebral oxygen extraction - Whitehead, Halana V. (Early Hum Dev, 2020)
BACKGROUND: Elevated cerebral fractional tissue oxygen extraction (cFTOE) is an adaptation to anemia of prematurity (AOP). cFTOE ≥0.4 is associated with brain injury in infants ≤30 weeks. This longitudinal study sought to investigate the utility of cFTOE in the evaluation of AOP. METHODS: Infants ≤30 weeks estimated gestational age (EGA) underwent weekly hemoglobin, cerebral saturation, and pulse oximetry recordings from the second through 36 weeks post-menstrual age (PMA). Recordings were excluded if they were under 1 hour or if hemoglobin was not measured within 7 days of recording. Mean cFTOE was calculated for each recording. Statistical analysis used linear mixed-effects modeling and receiver operating characteristic analysis. RESULTS: 144 recordings from 39 infants (mean EGA 27.6 ± 2.2 weeks, BW 1139 ± 286g) were included of whom 39% (15/39) were transfused. The mean recording length was 2.8 ± 1.3 hours. There was a significant negative correlation between hemoglobin and cFTOE (R = −0.423, p=<0.001). In a multivariate model, adjusting for EGA, PMA, and patent ductus arteriosus treatment the AUC was 0.821. A critical increase in cFTOE occurred at a hemoglobin level of 9.6 g/dL. CONCLUSIONS: AOP is associated with a critical increase in cFTOE that occurs at a significantly higher hemoglobin level than standard clinical thresholds for transfusion.